Photoluminescence research of the graphene quantum dots (GQD) interaction on the zinc oxide (ZnO) surface for application as H2O2 photosensor - Rolando Efraín Ramírez Garza; Sara Luisa Rodríguez de Luna; Idalia Gómez (Heliyon, 2024)
Photoluminescence (PL) spectroscopy is one of the best methods to detect molecules due to its easiness, fast time of analysis and high sensitivity. In addition, zinc oxide (ZnO) possesses good optical properties and particularly PL emission in these materials have been exploited for their potential use as photocatalyst, light harvesting and photosensor. These PL properties enhance when graphene quantum dots (GQD) are added to ZnO. For these reasons, we investigated the PL performance of ZnO-GQD nanocomposites. In one experiment we evaluated the PL emission of solid samples ZnO and ZnO-GQD. In a second experiment, these samples were also evaluated in aqueous phase to investigate the H2O2 effect during an experiment lasting 170 minutes. Both experiments displayed six peaks and they were related to the same PL emission source. The PL emission peak around 415 nm was found to be principal source where GQD are interacting. By varying the GQD amount to low, medium, and high concentration, the effect of H2O2 acted consequently, altering the PL emission during experiment in aqueous phase. An oxygen rich environment (ORE) occurred due to H2O2 which oxides the ZnO surface. Low GQD concentration resulted affected by an ORE weakening the GQD-ZnO contact, decreasing PL emission. In high GQD concentration, H2O2 induced GQD to reach the ZnO surface, increasing the PL emission. Only medium GQD concentration prevented oxidation of ZnO and maintained the PL emission intensity constant. When H2O2 concentration increased, for the medium GQD concentration, an excess of charge by peroxides inhibited the charge transfer from GQD to ZnO. This inhibition produces a quenching of the PL emission.